Cross-border acquisitions: Do labor regulations affect acquirer returns? - Levine, Ross; Lin, Chen; Shen, Beibei (Journal of International Business Studies, 2020)
Do cross-country differences in labor regulations shape (1) acquiring firms’ announcement returns and post-acquisition profits, costs, and revenues from cross-border deals, (2) the selection of cross-border targets, or (3) the success rates of cross-border offers? We discover that acquiring firms enjoy smaller abnormal returns and post-deal performance gains with targets in stronger labor protection countries; acquirers are more likely to purchase labor-dependent targets in weak labor regulation countries and more likely to use cross-border acquisitions to enter new markets when targets are in stronger labor regulation countries; and offer success rates fall when targets are in stronger labor regulation countries.